COVID-19 Pandemic Challenges for MSMEs: Strategic Options for Surviving in the New Normal Era - Saptono, Prianto Budi; Pratiwi, Intan (Jurnal Ekonomi dan Bisnis Jagaditha, 2022)
The purpose of this study is to analyze the obstacles faced by MSMEs during the COVID-19 outbreak; and to analyze various MSME survival strategies in dealing with the COVID-19 outbreak and the new normal era. This study employs descriptive qualitative methods. Secondary data is gathered from secondary sources such as books, scientific publications, government rules, and policies. Based on the findings of this study, it reveals that MSME actors must recognize the competitive advantages of their business. MSMEs can use social media marketing and record financial reports following SAK EMKM. MSMEs can use cloud accounting to streamline the accounting process, consider customer relationship marketing strategies, and follow health protocols in running their business workplace. Several ways are expected to help MSMEs in their role as the backbone of the nation's economy.